Prenatal diagnosis of 22q11.2 deletion syndrome associated with right aortic arch, left ductus arteriosus, cardiomegaly, and pericardial effusion - Yen-Ni Chen; Chih-Ping Chen; Tsang-Ming Ko; Liang-Kai Wang; Pei-Chen Wu; Tung-Yao Chang; Peih-Shan Wu; Chien-Wen Yang; Wayseen Wang (Elsevier, 2016)
Objective: To report prenatal diagnosis of 22q11.2 deletion syndrome with right aortic arch (RAA), left ductus arteriosus, cardiomegaly, and pericardial effusion in the fetus. Case report: A 35-year-old woman, gravida 2, para 1, was referred to the hospital at 31 weeks of gestation because of abnormal ultrasound findings and whole-genome array comparative genomic hybridization report. G-banding chromosome analysis revealed a karyotype of 46,XX. Level II ultrasound at 22 weeks of gestation revealed RAA with the presence of the aortic arch on the right side of trachea at three vessels and trachea view, left ductus arteriosus, and mild right side pyelectasis. Cardiomegaly and pericardial effusion were also found 2 months later. Array comparative genomic hybridization detected a 2.743-Mb deletion at 22q11.2 region. Multiplex ligation-dependent amplification detected deletion in the DiGeorge syndrome critical region of chromosome 22 low copy number repeat 22-A-C. Metaphase fluorescence in situ hybridization on lymphocyte in cord blood confirmed deletion in 22q11.2 region. Conclusion: Chromosome abnormalities have been found in patients with RAA. Prenatal diagnosis of RAA with or without intracardiac or extracardiac anomalies should include a diagnosis of 22q11.2 deletion syndrome.